Plastics and Inclusive Wealth - Pushpam Kumar (Journal of Moral Theology)
Plastic production, plastic waste disposal, and chemicals in plastics harm human health and well-being and create great inequity. Production of single-use plastics is especially harmful. The harms caused by plastics result in increased mortality and morbidity, which in turn undermine human capital and compromise sustainable growth in the inclusive wealth of nations. Exclusive use of Gross Domestic Product (GDP) as a metric of national wealth fails to measure these damages. The use of the Inclusive Wealth Index to supplement the GDP will provide a more comprehensive assessment of economy-environment interactions and better assess inequity than the GDP alone and can better guide ethically grounded, health-protective, and economically sound remedies to the global plastics crisis.